Design of a low-power and high-performance current sense amplifier - Teng, Terence Sze Chun. (2009)
Static Random Access Memory (SRAM) have been used extensively in the market especially in product such as the computer systems, hand-phones, digital camera and other electronic devices. A SRAM is a more expensive but faster and low power hungry memory when compared to DRAM. Users mainly use the SRAM due the mentioned characteristics. Thus, building a SRAM which consume lower power, faster reading speed and smaller package size is utmost important. Prior to discussion on building the SRAM, one of the more important internal structures of the SRAM is the sense amplifier. As the sense amplifier consume substantial amount of power and is also one of the device in the SRAM that affects its reading speed.